Optimal Location Selection for Mega-Kitchens in the Network Design of Free Lunch Programs in Nusa Tenggara Barat - Adji Candra Kurniawan; Anak Agung Ngurah Perwira Redi; Delinda Amarajaya; Theodora Rinda Hernawati; I Dewa Gde Yogindra Adipramana (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This study addresses the optimization of the supply chain network for the free lunch program in West Nusa Tenggara, Indonesia, aiming to enhance operational efficiency and service quality. The primary objective was to determine the optimal number and locations of mega-kitchens required to ensure efficient and timely meal delivery to various elementary schools across the region. Employing a combination of Greenfield Analysis (GFA) and simulation techniques within the anyLogistix software, the research systematically improved the supply chain configuration across five iterative simulations. The initial setup, with only one mega-kitchen, resulted in a 45% Expected Lead Time (ELT) Service Level, highlighting significant inefficiencies. Progressive iterations incorporated additional mega-kitchens, leading to substantial improvements in service levels and reductions in transportation costs. By the fifth iteration, the introduction of a fifth mega-kitchen achieved a perfect 100% ELT Service Level, demonstrating optimal operational efficiency with significant cost reductions. The findings confirm that strategic increases in the number of mega-kitchens, coupled with optimal location planning, significantly enhance the service delivery framework, meeting logistic demands while aligning with regional health and nutrition goals. This study illustrates the efficacy of advanced simulation tools in strategic planning and provides a scalable model for similar public health initiatives globally. Future research could explore more complex scenarios, including multi-modal transportation options and variable demand forecasts, to refine the operational efficiencies of such critical service delivery programs further.